The Prognostic Value of Peripheral Artery Diseases in Patients with ST-Segment Elevation Myocardial Infarction - Barbarash, Olga L.; Zykov, Mikhail V.; Pecherina, Tamara B.; Kashtalap, Vasily V.; Barbarash, Leonid S.; Kutikhin, Anton G. (Disease Markers, 2013)
Hypothesis. To evaluate the clinical and prognostic role of haemodynamically insignificant stenosis of the extracranial arteries (ECA) and lower extremity arteries (LEA) among patients with ST-segment elevation myocardial infarction (STEMI). Patients and Methods. The study sample consisted of 423 patients with STEMI who were consecutively admitted to the Kemerovo Cardiological Centre. Results. The prevalence of polyvascular diseases (PVD), as defined by an increased intima-media thickness (IMT) of the common carotid artery or by stenosis of the ECA or LEA, was 95%. Among patients with ECA or LEA, the case fatality rate of those with stenosis with occlusion of less than 30% of the vessel lumen was 5.7%, whereas the case fatality rate among patients with stenosis with occlusion of more than 30% of the vessel lumen was 15.1% (χ2=13.68, P=0.003). Using the GRACE score model, together with the determination of additional factors (congestive heart failure, PVD, prior stroke, and smoking status), we developed an improved model (KemScore) for death risk stratification for a 12-month period. The value of the AUC for our model (KemScore) was 0.83 (95% CI = 0.76–0.90), which was significantly higher than the initial GRACE score value of 0.71 (95% CI = 0.63–0.79).